Markers of achievement for assessing and monitoring gender equity in a UK National Institute for Health Research Biomedical Research Centre: A two-factor model - Henderson, LR; Shah, SGS; Ovseiko, PV; Dam, R; Buchan, AM; McShane, H; Kiparoglou, V (Public Library of Science, 2020)
Background The underrepresentation of women in academic medicine at senior level and in leadership positions is well documented. Biomedical Research Centres (BRC), partnerships between leading National Health Service (NHS) organisations and universities, conduct world class translational research funded by the National Institute for Health Research (NIHR) in the UK. Since 2011 BRCs are required to demonstrate significant progress in gender equity (GE) to be eligible to apply for funding. However, the evidence base for monitoring GE specifically in BRC settings is underdeveloped. This is the first survey tool designed to rank and identify new GE markers specific to the NIHR BRCs. Methods An online survey distributed to senior leadership, clinical and non-clinical researchers, trainees, administrative and other professionals affiliated to the NIHR Oxford BRC (N = 683). Participants ranked 13 markers of GE on a five point Likert scale by importance. Data were summarised using frequencies and descriptive statistics. Interrelationships between markers and underlying latent dimensions (factors) were determined by exploratory and confirmatory factor analyses. Results The response rate was 36% (243 respondents). Respondents were more frequently female (55%, n = 133), aged 41–50 years (33%, n = 81), investigators (33%, n = 81) affiliated to the BRC for 2–7 years (39.5%, n = 96). Overall participants ranked ‘BRC senior leadership roles’ and ‘organisational policies on gender equity’, to be the most important markers of GE. 58% (n = 141) and 57% (n = 139) respectively. Female participants ranked ‘organisational policies’ (64.7%, n = 86/133) and ‘recruitment and retention’ (60.9%, n = 81/133) most highly, whereas male participants ranked ‘leadership development’ (52.1%, n = 50/96) and ‘BRC senior leadership roles’ (50%, n = 48/96) as most important. Factor analyses identified two distinct latent dimensions: “organisational markers” and “individual markers” of GE in BRCs. Conclusions A two-factor model of markers of achievement for GE with “organisational” and “individual” dimensions was identified. Implementation and sustainability of gender equity requires commitment at senior leadership and organisational policy level.